Alpha acids content in Czech hops from 2024 harvest – forecasts, reality and trends - Alexandr Mikyška; Lucie Dolejší; Kateřina Dubnová; Karel Krofta; Gabriela Fritschová; Ivo Klapal; František Kroupa; Veronika Radilová (Kvasný průmysl)
The alpha acids content of the 2024 hop crop in the Czech Republic was evaluated using a pre-harvest forecast, a harvest forecast and a reality. The alpha-acids value in the Saaz variety was 2.72% w/w, in the Žatec (2.87% w/w) and Tršice (2.47% w/w) hop growing regions the content was well below the long-term averages, and in the Úštěk region (3.38% w/w) it was in line with the average. In Žatec and Úštěk, the alpha acids of the most widely cultivated hybrid varieties Sládek (7.5 and 6.7% w/w) and Premiant (7.5 and 8.5% w/w) were significantly higher than in Tršice (Sládek 4.8% w/w, Premiant 6.0% w/w). The values of the varieties Saaz Late and Saaz Special were below the average, while Kazbek (6.49% w/w) showed a good tolerance to weather conditions and the alpha acids content slightly above the average. The bitter varieties Agnus, Rubín and Vital with alpha acids content of 11–13% w/w give very stable alpha acids values over the long term, with 2024 corresponding to previous vintages. The harvest forecasts for alpha acids this year were in a very good agreement with reality. The year 2024 was relatively rich in water, but the distribution of rainfall over time was not optimal. Average monthly temperatures during the growing season were 1–2 °C above long-term averages, and the year as a whole was very warm. The Czech Republic's hop harvest (total of 6494 tonnes, yield 1.34 t/ha) was average in 2024. The total alpha acids production from the 2024 harvest was average at 242.5 t. The Saaz hops (82.1 % of the harvested area) accounted for 55% of the total. Bitter hop varieties cope better with adverse weather conditions than aromatic varieties.